Fauna of sone groups of invertebrates of Erebuni State Reserve (Armenia - L. S. Mirumyan; R. G. Harutyunyan; M. A. Marjanyan; V. S. Hovhannisyan; A. A. Avetisyan; N. Ch. Akopyan; M. Z. Magomedova; P. D. Magomedova; M. G. Ghasabyan; L. D. Harutyunova (Юг России: экология, развитие)
Aim. The aim of the work is to research the fauna of invertebrates in the Erebuni State Reserve.   Material and Methods. As research material served invertebrates gathered in the Erebuni State Reserve. The work was carried out at the Scientific Centre for Zoology and Hydroecology, National Academy of Sciences, Republic of Armenia in the period 2019–2023. The material was from our own collections, as well as from collections of insects and mollusks of the Institute of Zoology. The identification and collection of insects and mollusks were done using standard methods.   Results. An overview of some groups of invertebrates in the Erebuni State Reserve is here provided for the first time. As a result of the research, 35 species of Diptera, 15 species of Coleoptera, 44 species of Lepidoptera,10 species of aphids and 12 species of mollusks were identified. Some species are listed in the “Red Book” of Armenia and are under the protection of the state, and there are rare species and species found in the Republic of Armenia only in the reserve. 15 species of insects identified by us develop on 4 plant species included in the “Red Book” of Armenia.   Conclusion. The Erebuni State Reserve is represented by a rather diverse and valuable fauna of invertebrates studied by us, including a number of rare and protected species. Species of invertebrates associated in their development with valuable wild, economically important and protected plants have been identified in the reserve. Identification of species diversity and trophic relationships of some groups of insects that develop on rare and protected plants of the reserve is relevant for natural areas under state protection, of which the Erebuni State Reserve is one.